A How-to Guide to Building a Robust SARS-CoV-2 Testing Program at a University-Based Health System - Stephen D. Nimer MD; Jennifer Chapman MD; Lisa Reidy PhD; Alvaro Alencar MD; YanYun Wu MD, PhD; Sion Williams PhD; Lazara Pagan MSN; Lauren Gjolaj MBA; Jessica MacIntyre MSN; Melissa Triana MBA; Barbara Vance PhD; David Andrews MD; et al. (Elsevier, 2020)
When South Florida became a hot spot for COVID-19 disease in March 2020, we faced an urgent need to develop test capability to detect SARS-CoV-2 infection. We assembled a transdisciplinary team of knowledgeable and dedicated physicians, scientists, technologists, and administrators who rapidly built a multiplatform, polymerase chain reaction- and serology-based detection program, established drive-through facilities, and drafted and implemented guidelines that enabled efficient testing of our patients and employees. This process was extremely complex, due to the limited availability of needed reagents, but outreach to our research scientists and multiple diagnostic laboratory companies, and government officials enabled us to implement both Food and Drug Administration authorized and laboratory-developed testing-based testing protocols. We analyzed our workforce needs and created teams of appropriately skilled and certified workers to safely process patient samples and conduct SARS-CoV-2 testing and contact tracing. We initiated smart test ordering, interfaced all testing platforms with our electronic medical record, and went from zero testing capacity to testing hundreds of health care workers and patients daily, within 3 weeks. We believe our experience can inform the efforts of others when faced with a crisis situation.